Development and performance test of a miniature movable mixed-refrigerant liquid nitrogen generator. (December 2018) - Wang, H.C.; Guo, H.; Zhao, Y.X.; Chen, G.F.; Gong, M.Q.
Highlights: Full air-cooled small movable LN2 generator for remote and field users. Using normal refrigeration equipment, low cost and high reliability. Various low pressure gas sources, using small commercial air compressors. Closed N2 cycle to deliver cooling capacity between flammable MRJT and air. Simplified configuration and operation of mini air separation column. Abstract: In order to cover long-term but small quantity liquid nitrogen requirements of laboratory or field users, a miniature movable mixed-refrigerant liquid nitrogen generator (MRLN) was developed and tested here, based on a precooled mixed-refrigerant J-T (MRJT) refrigerator. With the full air-cooled, skid-mounted structure, this MRLN was built utilizing off-the-shelf refrigeration components like commercial single-stage oil-lubricated compressors to reduce construction cost greatly. Bottled pure N2, pressure swing adsorption (PSA) unit and mini cryogenic rectification column could be employed to supply N2 in different operation modes respectively. In pure N2 mode, N2 was directly liquefied by the MRJT refrigerator. With feed N2 at 0.8 MPa, the specific power consumption ( SPC ) was 1.79 kWh L −1, and figure of merit ( FOM ) was 6.27%. The estimated SPC in PSA mode was 2.68 kWh L −1 . For column mode, the SPC was 4.59 kWh L −1, with FOM of 3.38%. A closed N2 cycle could convey cooling capacity between flammable refrigerant and air. This MRLN could be a convenient and low-costing choice for some liquid nitrogen users.